Gestão estratégica para pequenas empresas em estágio crítico de desenvolvimento : uma proposta de modelo sistematizando as informações e os recursos humanos - Chu, Marilia Gabriela Pavan Kuri (Universidade Federal de São Carlos, 2010)
The main purpose of this work is to establish a Strategic Management Model which includes the peculiar situation of small companies in a shifting moment of their life cycle. In a critical moment of restructuring in small companies the systematization of Human Resources HR and Information Systems IS were found crucial to the efficiency of the Strategic Management process. The modeling proposal shows Human Resources and Information Systems not only as support areas to the Competitive Strategy, but also as fundamental elements to constitute efficient Strategic Management. Two small companies were studied using action-research method. It has been shown that an organization needs to sustain data collection which feeds strategic diagnosis, as well as keep compromised with strategic goals coworkers who make feasible action programs. Defined as infrastructural priorities, HR and IS are the foundation to the Competitive Strategy. The core of strategy concepts has not been altered, so it is consonant with several authors in this field of knowledge. It has been concluded that Strategy is about create unique value, which means to be different somehow and therefore have added value and profits. That implies to develop value chain in business with several competitive advantages that may be isolated to be copied, but they hardly will be copied as a whole. Companies have to obtain, from all technological, human and financial resources, among others, an ideal combination of their usage in real time so they can get competitive gains in the business. Therefore, this is the main role of Competitive Strategy: to create to managers a sustainable cycle to evaluate, criticize and change decisions that have been and will be taken to business growth, establishing criteria that help to understand and reverse negative outcomes and to make feasible and maximize positive effects. This work has shown some difficulties found in the stage shifting of life cycle in the small companies, for which the lack of HR and SI structure may cause severe damage to all strategic actions, since data and labor teams become compromised.
Keywords: Organização da produção; Estratégia competitiva; Pequenas e médias empresas; Recursos humanos; Sistemas de informação; Gestão estratégica; Strategic management; Small company; ENGENHARIAS::ENGENHARIA DE PRODUCAO